Annao Pingchong decoction attenuates oxidative stress and neuronal apoptosis following intracerebral hemorrhage via RAGE-NOX2/4 axis - Wang, Xu; Lin, Xiaoyuan; Chen, Zilin; Long, Hongping; Zhou, Xuqing; Lei, Shihui; Liu, Jian; Dong, Huan; Liu, Fang; Hu, Hua; Guo, Chun (Frontiers in Neuroscience, 2024)
BackgroundIntracerebral hemorrhage (ICH) is a severe condition associated with high mortality and disability rates. Oxidative stress plays a critical role in the development of secondary brain injury (SBI) following ICH. Previous research has demonstrated that Annao Pingchong decoction (ANPCD) treatment for ICH has antioxidant effects, but the exact mechanism is not yet fully understood.ObjectiveThis study aimed to investigate the neuroprotective effects of ANPCD on oxidative stress and neuronal apoptosis after ICH by targeting the receptor for advanced glycation end products (RAGE)-NADPH oxidase (NOX) 2/4 signaling axis.MethodsThe research involved the creation of rat ICH models, the mNSS assay to assess neurological function, Nissl staining to evaluate neuronal damage, and biochemical assays to measure oxidative and antioxidant levels. The expression of RAGE-NOX2/4 axis proteins was analyzed using western blotting and immunofluorescence, while neuronal apoptosis was assessed with TUNEL staining. Furthermore, after performing quality control of drug-containing serum using UPLC-MS/MS, we employed an in vitro model of heme-induced injury in rat cortical neurons to investigate the neuroprotective mechanisms of ANPCD utilizing RAGE inhibitors.ResultsThe findings indicated that ANPCD improved neurological deficits, reduced neuronal damage, decreased ROS and MDA levels, and increased the activities enzymatic activities of SOD, CAT, GSH and GPX. Additionally, it suppressed the RAGE-NOX2/4 signaling axis and neuronal apoptosis.ConclusionANPCD exhibits neuroprotective effects by inhibiting the RAGE-NOX2/4 signaling axis, thereby alleviating neuronal oxidative stress and apoptosis following ICH.